Penerapan Prinsip 5c pada Pembiayaan Murabahah di SUMUT Syariah KCP HM Yamin - Alwi Muarif Sembirin; Nurul Jannah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The purpose of the study was to determine the supporting and inhibiting factors in Murabahah financing at Bank SUMUT Syariah KCP HM Yamin and the application of 5C principles to Murabahah financing at Bank SUMUT Syariah KCP HM Yamin. The research method used is descriptive qualitative research... Information obtained from interviews, literature review sourced from journals and critical thinking from the author. Based on the results of the author's research at Bank SUMUT Syariah Kcp HM. Yamin. So what can be concluded from the company where the author carries out practical internship work, namely as follows; PT Bank Sumut which is one of the tools/equipment of regional autonomy in the banking sector, PT Bank Sumut has a function as a driver and driver of the pace of development in the region, acting as a regional treasury holder and or carrying out regional money storage as well as a source of regional income and as a source of regional income. Commercial banks. The government considers PT Bank Sumut to be able to bounce back and considering the important role of PT Bank Sumut in supporting development in the North Sumatra area, the government only includes PT Bank Sumut in recapitalized banks.